Phosphatidylserine-targeting antibodies augment the anti-tumorigenic activity of anti-PD-1 therapy by enhancing immune activation and downregulating pro-oncogenic factors induced by T-cell checkpoint inhibition in murine triple-negative breast cancers. Issue 1 (December 2016) - Gray, Michael; Gong, Jian; Hatch, Michaela; Nguyen, Van; Hughes, Christopher; Hutchins, Jeff; Freimark, Bruce
Abstract Background The purpose of this study was to investigate the potential of antibody-directed immunotherapy targeting the aminophospholipid phosphatidylserine, which promotes immunosuppression when exposed in the tumor microenvironment, alone and in combination with antibody treatment towards the T-cell checkpoint inhibitor PD-1 in breast carcinomas, including triple-negative breast cancers. Methods Immune-competent mice bearing syngeneic EMT-6 or E0771 tumors were subjected to treatments comprising of a phosphatidylserine-targeting and an anti-PD-1 antibody either as single or combinational treatments. Anti-tumor effects were determined by tumor growth inhibition and changes in overall survival accompanying each treatment. The generation of a tumor-specific immune response in animals undergoing complete tumor regression was assessed by secondary tumor cell challenge and splenocyte-produced IFNγ in the presence or absence of irradiated tumor cells. Changes in the presence of tumor-infiltrating lymphocytes were assessed by flow cytometry, while mRNA-based immune profiling was determined using NanoString PanCancer Immune Profiling Panel analysis. Results Treatment by a phosphatidylserine-targeting antibody inhibits in-vivo growth and significantly enhances the anti-tumor activity of antibody-mediated PD-1 therapy, including providing a distinct survival advantage over treatment by either single agent. Animals in which complete tumor regression occurred with combination treatments were resistant to secondary tumor challenge and presented heightened expression levels of splenocyte-produced IFNγ. Combinational treatment by a phosphatidylserine-targeting antibody with anti-PD-1 therapy increased the number of tumor-infiltrating lymphocytes more than that observed with single-arm therapies. Finally, immunoprofiling analysis revealed that the combination of anti-phosphatidylserine targeting antibody and anti-PD-1 therapy enhanced tumor-infiltrating lymphocytes, and increased expression of pro-immunosurveillance-associated cytokines while significantly decreasing expression of pro-tumorigenic cytokines that were induced by single anti-PD-1 therapy. Conclusions Our data suggest that antibody therapy targeting phosphatidylserine-associated immunosuppression, which has activity as a single agent, can significantly enhance immunotherapies targeting the PD-1 pathway in murine breast neoplasms, including triple-negative breast cancers.